Step * 2 of Lemma regular-upto-iff


1. : ℕ+
2. : ℕ+
3. : ℕ+ ⟶ ℤ
4. ∀n,m:ℕ+1.
     let seq-min-upper(k;b;x) in
      let (r((x j) (2 k))/r((2 k) j)) in
      (((r((x n) k)/r((2 k) n)) ≤ z) ∧ (z ≤ (r((x n) (2 k))/r((2 k) n))))
      ∧ ((r((x m) k)/r((2 k) m)) ≤ z)
      ∧ (z ≤ (r((x m) (2 k))/r((2 k) m)))
⊢ ↑regular-upto(k;b;x)
BY
((RWO "assert-regular-upto" THENA Auto) THEN RepeatFor (ParallelLast')) }

1
1. : ℕ+
2. : ℕ+
3. : ℕ+ ⟶ ℤ
4. : ℕ+1
5. : ℕ+1
6. let j@0 seq-min-upper(k;b;x) in
    let (r((x j@0) (2 k))/r((2 k) j@0)) in
    (((r((x i) k)/r((2 k) i)) ≤ z) ∧ (z ≤ (r((x i) (2 k))/r((2 k) i))))
    ∧ ((r((x j) k)/r((2 k) j)) ≤ z)
    ∧ (z ≤ (r((x j) (2 k))/r((2 k) j)))
⊢ |(i (x j)) (x i)| ≤ ((2 k) (i j))


Latex:


Latex:

1.  k  :  \mBbbN{}\msupplus{}
2.  b  :  \mBbbN{}\msupplus{}
3.  x  :  \mBbbN{}\msupplus{}  {}\mrightarrow{}  \mBbbZ{}
4.  \mforall{}n,m:\mBbbN{}\msupplus{}b  +  1.
          let  j  =  seq-min-upper(k;b;x)  in
            let  z  =  (r((x  j)  +  (2  *  k))/r((2  *  k)  *  j))  in
            (((r((x  n)  -  2  *  k)/r((2  *  k)  *  n))  \mleq{}  z)  \mwedge{}  (z  \mleq{}  (r((x  n)  +  (2  *  k))/r((2  *  k)  *  n))))
            \mwedge{}  ((r((x  m)  -  2  *  k)/r((2  *  k)  *  m))  \mleq{}  z)
            \mwedge{}  (z  \mleq{}  (r((x  m)  +  (2  *  k))/r((2  *  k)  *  m)))
\mvdash{}  \muparrow{}regular-upto(k;b;x)


By


Latex:
((RWO  "assert-regular-upto"  0  THENA  Auto)  THEN  RepeatFor  2  (ParallelLast'))




Home Index